The Implementation of Storyboarding Technique to Improve Writing Skill of the Ninth Grade Students of SMP Negeri 5 Sigi - Putri Nabilah; Konder Manurung; Andi Patmasari; Budi Budi (MASI Mandiri Edukasi, 2025)
This study aims to investigate the effect of the Storyboarding Technique in improving the writing skills of ninth-grade students at SMP Negeri 5 Sigi. The primary issue addressed is students' difficulty generating and organizing ideas while maintaining motivation during writing activities. The research adopts a quasi-experimental design with a pretest-posttest control group involving two classes selected through simple random sampling: experimental and control classes. The research instruments included pre-test and post-test assessments. In the pre-test, the experimental group scored an average of 42, while the control group scored 44.16. After the treatment, the post-test scores increased to 67.83 for the experimental group and 58.16 for the control group. Statistical analysis using degrees of freedom (df) 46 at a significance level of 0.05 showed that the t-count (2.006) exceeded the t-table (1.678), indicating a significant difference. The results demonstrate that the Storyboarding Technique effectively improves students' writing skills, particularly in recount text composition. This technique motivates students by facilitating idea visualization and structuring before formal writing. The findings suggest that teachers may integrate storyboarding as a creative approach to English language learning to enhance students' writing proficiency. Further research is recommended to explore its long-term effects on writing development.